Does the core circadian clock in the moss Physcomitrella patens (Bryophyta) comprise a single loop? - Hedman Harald; Gyllenstrand Niclas; Källman Thomas; Holm Karl; Lagercrantz Ulf (BMC Plant Biology, 2010)
Abstract Background The endogenous circadian clock allows the organism to synchronize processes both to daily and seasonal changes. In plants, many metabolic processes such as photosynthesis, as well as photoperiodic responses, are under the control of a circadian clock. Comparative studies with the moss Physcomitrella patens provide the opportunity to study many aspects of land plant evolution. Here we present a comparative overview of clock-associated components and the circadian network in the moss P. patens. Results The moss P. patens has a set of conserved circadian core components that share genetic relationship and gene expression patterns with clock genes of vascular plants. These genes include Myb-like transcription factors PpCCA1a and PpCCA1b, pseudo-response regulators PpPRR1-4, and regulatory elements PpELF3, PpLUX and possibly PpELF4. However, the moss lacks homologs of AtTOC1, AtGI and the AtZTL-family of genes, which can be found in all vascular plants studied here. These three genes constitute essential components of two of the three integrated feed-back loops in the current model of the Arabidopsis circadian clock mechanism. Consequently, our results suggest instead a single loop circadian clock in the moss. Possibly as a result of this, temperature compensation of core clock gene expression appears to be decreased in P. patens. Conclusions This study is the first comparative overview of the circadian clock mechanism in a basal land plant, the moss P. patens. Our results indicate that the moss clock mechanism may represent an ancestral state in contrast to the more complex and partly duplicated structure of subsequent land plants. These findings may provide insights into the understanding of the evolution of circadian network topology.